Redesigning pharmacy delivery processes of a health care complex. - Augusto V; Xie X; Augusto, Vincent; Xie, Xiaolan (Health Care Management Science, 2009)
This paper addresses a pharmacy delivery design problem with two types of human resources: pharmacy assistants and transporters within a hospital. Each medical unit of the hospital has a mobile medicine closet which is conveyed each week by transporters to the central pharmacy for inventory assessment and refill by assistants. Transportation is carried out by foot, by tractor or by truck depending on the location. The problem consists in creating a transportation and supply planning for each day of the week in order to balance workloads for both transporters and assistants while ensuring the availability of medicine to each medical service. A two-step approach using mixed-integer linear programming formulation is proposed to determine a near optimal schedule. Numerical results are given to assess its efficiency. The proposed approach is then combined with a simulation model to redesign the delivery process of the pharmacy department of a French university teaching hospital. Methodology of this real-life reengineering study is presented and discussed.